Ayurveda and Siddha systems polyherbal formulations to treat COVID-19 caused by SARS-CoV-2 and brief insight on application of Molecular Docking and SWISS Target prediction tools to study efficacy of active molecules - Hemanth Kumar Manikyam; Sunil K Joshi; Malinidevi M; Afeefa Noor (International Journal of Phytomedicine, 2020)
Ayurveda and Siddha systems are the two ancient medical systems originated in India more than 4000 years ago had given many formulary and treatment methods against influenza like infections. Kabasura churan from Siddha system and Maha sudharshan churan from the Ayurvedic system are the two major formulations along with many other individual herbs mentioned in the texts to treat Influenza like infections. Kabasura churan and Maha Sudarshan churan both have antipyretic, analgesic and anti-inflammatory effects. Both formulations were prepared according to Siddha and Ayurvedic texts. Herbs mentioned in both formulations like Turmeric, Tulsi (Basil), Kalmegh (Andrographis), Black Pepper, Liquorice (Mulethi), and Dronapushpi (Leucas) etc., had direct antiviral effect. Herbs like Aswagandha, Ginger, Guduchi (Tinospora), Kulanjan (Galangal) etc., had immunomodulatory and anti-inflammatory effect. Active compounds from different herbs were selected to study their antiviral activity through molecular docking algorithm. Application of modern of tools like Bioinformatics and Highthroughput screening methods can predict the efficacy of the ancient documented formulations and can be compared as per their literature. Compounds like curcumin, Glycyrrhizin, Ursolic acid, Quercetin, Andrographolide, Coumarins etc. were showed polyspecific activity like inhibition of Spike protein, Furin, Main Protease (Mpro) and Papain like Proteases (PLpro). Thus we propose use of Kabasura churan and Maha Sudharshan churan as alternative complementary medicine as a palliative treatment against COVID-19 caused by SARS-CoV-2 by conducting proper Randomized Clinical Trials